ANALISIS PEMIKIRAN IBRAHIM MUSTHAFA DALAM PERKEMBANGAN ILMU NAHWU: ANALISIS KRITIS DAN EPISTEMOLOGIS - Candra Agus Saputra; Muhammad Attila Rifiananda; Akhmad Aliudin; Fauzi Ridwan (SIRAJUDDIN : Jurnal Penelitian dan Kajian Pendidikan Islam, 2025)
This study aims to examine the thoughts of Ibrāhīm Muṣṭafā in the renewal of Arabic grammar (nahwu) through a critical and epistemological approach. Recognized as a reformist in Arabic linguistics, Ibrāhīm Muṣṭafā sought to simplify and modernize traditional nahwu to make it more functional, communicative, and relevant to contemporary language learning needs. In his seminal work Iḥyā’ an-Naḥwi, he presents sharp critiques of the complexities of classical grammar, particularly the concept of ‘āmil, the i‘rāb system, and the excessive reliance on speculative analogical reasoning. This research uses a qualitative library research method with an epistemological-comparative analysis, especially by contrasting the perspectives of Ibrāhīm Muṣṭafā with those of Imam Sībawaih, the foundational figure of classical nahwu. The findings reveal that Ibrāhīm Muṣṭafā offers a deep transformation in structure, terminology, and teaching methods of nahwu, making it simpler and more meaningful. His ideas represent a paradigm shift from a rigid textual tradition to a practical and contextual linguistic framework, bridging classical heritage with modern linguistic discourse.